El ‘principio del orden” como meta-principio último de la racionalidad leibniziana - Nicolás, Juan Antonio (2014)
Proposed here is a partial reconstruction of Leibniz’s metaphysics as an “ontology of the systemic individuality“. It is a reconstructive spherical-axial model, concerning three categorical axes: Individuality-systematicity, uniformity- diversity and vitality-functionality. This formal structure is systematized through a last meta-principle (“principle of the general order”) that incorporates the perspective of the finitness of reason.